Estudos sobre a implementação da educação ambiental na formação acadêmica do designer - Marinho, Alexandre Luiz (2008)
This work was designed to contribute to the knowledge and experience on how integration of sustainability issues in regular design course can be accomplished. As an overview of Brazilian design courses, it was recognized the lack of environmental subjects in the majority of the design undergraduate courses program, especially in product development. The continuously evolving portfolio of courses offered at Design department of Positivo University was systematically discussed, with a focus on environmental content, course formats, assignments and lessons learned from course evaluations in recent years. The main objective of this work was to provide a useful overview for any teacher and/or curriculum developer wishing to integrate sustainability into design programs. In order to encourage the environmental concern of the Positivo University students of Design department, an environmental chemistry short course of ten hours was offered to some students. The assimilation of environmental concepts of the course was accessed by qualitative and quantitative questionnaire applied to the participants. The results were evaluated in comparison with similar experiences done at TU Delft University, Holland, pointing out that this isolate action does not incorporate the environmental responsibility to the students. However, some students interested in sustainability issues, showed a pro-active and positive attitude towards integrating sustainability concerns into what is to become their professional careers as designers. It has been pointed out that in the experience of TU Delft, communicating sustainability criteria is most successfully when done in an integrative setting, mimicking real life design problems. There, students learn to face the challenge of addressing multiple criteria. Making them think on how to solve such dilemmas, through discussion, through letting them create their own tools, or even by letting them experience themselves in which cases environmental concerns will often be outweighed by more traditional business criteria, makes students more realistic on one hand, but also more aware of how to channel their positive attitude towards good design solutions that are likely to get implemented. The curriculum of ECO-Design was proposed as snapshot in time. Developments in society make that the development of course material never comes to a halt. Especially in the field of sustainable product design, with its multidisciplinary nature as well as fast societal developments, this is true. It is expected that in the years to come, new topics related to sustainability thinking will find their way into the various environmental Design issues. Discussions are on the way about the integration of sustainability into this new curriculum proposed.